The Nurses' Experience in Providing Health Care for Criminals in General Hospital - Wirmando, Wirmando; Astari, Asti Melani; Yuliatun, Laily (Fakultas Kedokteran Universitas Brawijaya, 2021)
Providing health care for criminals is very complex, stressful, and challenging for the general hospital nurses who are usually not habituated to treat them. The nurses are required to keep their caring and professional work. Providing health care for criminals puts the nurses into a risky working environment. They are susceptible to physical and psychological aggressions that can influence their practices and their applied nursing care quality. The objective of this research is to explore the general hospital nurses' experience in providing health care for the criminals. This is qualitative method research with a phenomenological approach. The data collection was done by a deep interview for 10 nurses. The applied data analysis is the Interpretative Analysis Phenomenology (IPA). The six themes found in the research are: 1) feeling discomfort in working, 2) experiencing emotional conflict, 3) working in an unsafe environment, 4) having difficulties in creating a therapeutic relationship, 5) unnatural caring emergence, and 6) not wanting the police officers to get involved in treating the patients. The security and emotional feeling factors of the nurses become the greatest challenges. They make the nurses difficult to create a therapeutic relationship and lead to unnatural caring committed by the nurses. Therefore, it is important for the nurses to internalize and reflect sincere caring as the essential principles in the nursing profession. Thus, it can reach the objectives of nursing, service equality, and patient recovery.